Active defence mechanisms in brood parasitism hosts and their consequences for parasite adaptation and speciation - Guillaume Dillenseger (Journal of Avian Biology)
Obligate brood parasitism is a peculiar behaviour found in some bird species. The costs for their hosts can be high, generating selection for active defence strategies including foreign egg and chick rejection. Only one of these two rejection strategies seems to be expressed in any given host species, which in turn selects for mimicry in parasites only at one stage of the nesting cycle. Here, I review the cues used by hosts to recognise brood parasites in the nest and the behaviours to neutralise them, as well as counteradaptations found in parasites. Furthermore, I link these adaptations with theoretical and known processes of genetic transmission of the involved mimicry traits to the offspring. I suggest that the stage at which the parasite is recognised by the host can impose selection on the mating system of the parasite and increase the likelihood of speciation. When hosts discriminate against foreign eggs, interbreeding by male and female parasites reared by different hosts may impede speciation, but not the evolution of egg mimicry if inherited through the maternal line (via the W‐chromosome). When hosts discriminate against chicks, an effective mimetic phenotype requires autosomal (or Z‐chromosome) inheritance to allow expression in both male and female chicks, thus favouring assortative mating in the parasites, and potentially leading to speciation. To my knowledge, this review is the first to link host defence strategies with their potential consequences for speciation in brood parasites. I suggest future steps to fill knowledge gaps in brood parasitism.